2018
DOI: 10.1002/hpm.2588
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Brazilian public services of kidney transplantation: Benchmarking Brazilian states via data envelopment analysis

Abstract: an innovative context of application and may be useful for the community of relevant policymakers, academics, and health professionals. KEYWORDS Brazilian health system, data envelopment analysis, efficiency assessment, kidney transplant 1 | INTRODUCTION End-stage renal disease is a serious public health issue in which patient survival depends on renal transplantation or renal replacement therapy, such as dialysis. 1 In the long term, however, kidney transplantation is generally more effective than dialysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 76 publications
(86 reference statements)
2
7
2
Order By: Relevance
“…This study also identified a change in the efficiency frontier from 2006 to 2011 but did not reveal progress in productivity. Similar results were found by Siqueira and Araujo [ 9 ], in a study using data from 2013 to 2015 that examined the technical and scale efficiency of Brazilian public services in kidney transplantation. This study also showed that states from the South and Southeast regions in Brazil performed better when compared to the poorest states from the North and the Northeast.…”
Section: Background and Literature Reviewsupporting
confidence: 87%
See 4 more Smart Citations
“…This study also identified a change in the efficiency frontier from 2006 to 2011 but did not reveal progress in productivity. Similar results were found by Siqueira and Araujo [ 9 ], in a study using data from 2013 to 2015 that examined the technical and scale efficiency of Brazilian public services in kidney transplantation. This study also showed that states from the South and Southeast regions in Brazil performed better when compared to the poorest states from the North and the Northeast.…”
Section: Background and Literature Reviewsupporting
confidence: 87%
“…In addition, these patients usually need to be in Intensive Care Units (UCI) as specific medical devices are required to maintain artificial breathing and hemodynamic functions. This is necessary to prevent cardiac arrest and ensure blood circulation [ 9 ] in order to “maintain adequate conditions for the organs to be subject to donation” (Garcia [ 10 : 23]). Then, the next step in the process is to obtain consent for organ donation.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations